Enhancing School-wide Positive Behavioral Interventions and Supports Tier 1 core practices to improve disciplinary equity. Issue 4 (2nd August 2021) - Bastable, Eoin; Falcon, Sarah Fairbanks; Nese, Rhonda; Meng, Paul; McIntosh, Kent
Abstract: Addressing racial disparities in school discipline is an urgent and widespread issue facing US schools. One approach to improve racial equity in school discipline practice is to enhance the contextual fit of empirically validated schoolwide practices. Schoolwide Positive Behavioral Interventions and Supports (SWPBIS) is a widely implemented and research-validated approach shown to improve behavioral and academic outcomes, yet evidence suggests students of color remain disproportionately disciplined in schools implementing the SWPBIS framework to fidelity. Contextual fit is a core principle of SWPBIS, but in practice, schools may lack effective strategies to enhance equity using the framework's tier 1 core practices. This article describes promising enhancements to universal school practices aimed at reducing school discipline disparities.